Cytotoxicity, antioxidant activity, total flavonoid and phenolic contents of Salvia urmiensis Bunge and Salvia hydrangea DC. ex Benth. - M.B. Bahadori; M. Mirzaei (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Salvia species are important because of their medicinal, traditional and economical uses. They are used traditionally for treatment of several diseases. The genus Salvia is represented in the Iranian flora by 61 species of which, 17 are endemic.  In the present study, the phytochemical and biological effects of two Iranian Salvia species have been evaluated. Methods: 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radicals scavenging activities of extracts of Salvia urmiensis Bunge and Salvia hydrangeawere evaluated. Total flavonoid and phenolic contents and brine shrimp lethality potential of the extracts were also determined. Results: Compared to podophyllotoxin (LC50 =42 µg/mL), the ethyl acetate extract of S. hydrangea demonstrated a significant cytotoxicity (LC50=36 µg/mL). The ethyl acetate extract of S. urmiensis was found to have significant antioxidant properties with IC50 value of 10.0±0.2 µg/mL. All tested extracts showed moderate to high flavonoid and phenolic contents. Conclusion: Findings showed that these plants contain important metabolites and could be suggested for discovery of biologically active natural compounds.